Avaliação do impacto de treinamento no trabalho: o caso do Instituto Nacional de Colonização e Reforma Agrária - INCRA - Souza, Gleicyane da Conceição (2018)
Higher competence levels are required of individuals so that they can act in a context of constant social changes. Many formal learning actions are given in the form of courses, in order to improve people's performance and the organizations' as well, but not always the skills acquired by the participants are used in work environment. Thus, this research aims to perform an impact assessment training of the Rural Environmental Cadastre, offered by Instituto Nacional de Colonização e Reforma Agrária – INCRA. To achieve the objectives of this research, a case study of descriptive nature was carried out with a predominantly quantitative approach, cross-sectional data and information collection from primary sources. An online questionnaire was used to data collection. The questionnaire was composed of sociodemographic characteristics of the participants and of two known instruments consolidated in literature (Training Impact Scale at Work and Training Transfer Support Scales). The sample consisted of 139 workers who participated in the training course, and to study the data collected, several types of analysis were employed as exploratory, descriptive, factorial (PCA), correlations and content analysis. The results revealed responses with favorable average to the Workload Impact Scale items, but lower values to the support scales. The Impact Scale was evaluated to different groups by comparing the sociodemographic characteristics of the sample. A content analysis was also performed through an open question, to determine participants' perception regarding the effectiveness of the training offered by the organization. The multiple scales from the factorial analysis presented excellent reliability indexes and the tested correlations were positive and significant among the variables proposed in the research model. From these results, it can be concluded that there was a favorable impact in the work environment, so that the people who took the course in a mandatory way perceived greater impact than those who opted for it on an optional basis.